Progression in Glaucoma: a snapshot - Abegão Pinto, Luis (Revista Sociedade Portuguesa de Oftalmologia, 2016)
The main goal of glaucoma management is to slow disease progression, so preserving functional vision as much as possible. Thus, accurate detection of structural and functional progression in glaucoma is essential for an effective patient care and to protect quality of life. However, from a clinical point of view, optimizing this detection remains a challenge for ophthalmologists worldwide. . We hereby review concepts and summarize current knowledge about interpreting the different methods to detect disease progression in glaucoma patients.